HUBUNGAN KETELADANAN GURU PENDIDIKAN AGAMA KRISTEN DAN PERHATIAN ORANG TUA DENGAN KARAKTER KRISTIANI PESERTA DIDIK: STUDI DI SMK NEGERI 1 SIGUMPAR KABUPATEN TOBA - Samuelson Halomoan Siagian; Lince Sihombing; Baginda Sitompul (STKIP Subang, 2026)
The purpose of this study was to determine the magnitude of the relationship between: 1) the exemplary behavior of Christian Religious Education teachers and the Christian character of students at SMK Negeri 1 Sigumpar; 2) parental attention and the Christian character of students at SMK Negeri 1 Sigumpar; and 3) the combined relationship between the exemplary behavior of Christian Religious Education teachers and parental attention with the Christian character of students at SMK Negeri 1 Sigumpar. The method used in this study was inferential quantitative research. The population consisted of all eleventh-grade students of SMK Negeri 1 Sigumpar, totaling 45 students. The instrument trial was conducted on 30 students at SMK Negeri 1 Laguboti, and all research instruments were declared valid and reliable because they met the validity and reliability criteria. Data were collected using a closed-ended questionnaire consisting of 80 items. The results of the data analysis showed that: 1) there was a relationship between the exemplary behavior of Christian Religious Education teachers and the Christian character of students at SMK Negeri 1 Sigumpar amounting to 27.1%, with Fvalue > Ftable, namely 15.994 > 3.23; 2) there was a relationship between parental attention and the Christian character of students at SMK Negeri 1 Sigumpar amounting to 37.5%, with Fvalue > Ftable, namely 25.791 > 3.23; and 3) there was a simultaneous relationship between the exemplary behavior of Christian Religious Education teachers and parental attention with the Christian character of students at SMK Negeri 1 Sigumpar amounting to 41.8%, with Fvalue > Ftable, namely 15.055 > 3.23. Therefore, Ha was accepted and H0 was rejected.